REPRESENTASI SOSIAL SUBALTERN WARIA DI KOTA DENPASAR - Rahayu Dewi, Ni Ketut Budi; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study presents an analysis of the efforts of social subaltern representation of transgender. Transgender as subalterns still have not received recognition in Denpasar City. The method used in this research is qualitative with descriptive-explanatory type of research, and analyzed using subaltern theory from Gayatri Spivak regarding efforts of transgender in Denpasar City to gain public recognition, considering that transgender in Denpasar City are one of the subalterns. Spivak intended to be minorities who are oppressed and unable to speak out, so they need intellectuals to represent their voices. Based on the research that has been done, to eliminate the negative stigma of a transgender, both transgender, and organizations such as the Gaya Dewata Foundation and the Bali Legal Aid Institute seek subaltern voices of transgender as vulnerable groups through progressive actions, among others; become participants in social, legal, economic and beauty activities. Keywords:Social representation, subaltern, transgender